Mechanisms and applications of radiation-induced oxidative stress in regulating cancer immunotherapy - Zheng, Zhuangzhuang; Su, Jing; Bao, Xueying; Wang, Huanhuan; Bian, Chenbin; Zhao, Qin; Jiang, Xin (Frontiers in Immunology, 2023)
Radiotherapy (RT) is an effective treatment option for cancer patients, which induces the production of reactive oxygen species (ROS) and causes oxidative stress (OS), leading to the death of tumor cells. OS not only causes apoptosis, autophagy and ferroptosis, but also affects tumor immune response. The combination of RT and immunotherapy has revolutionized the management of various cancers. In this process, OS caused by ROS plays a critical role. Specifically, RT-induced ROS can promote the release of tumor-associated antigens (TAAs), regulate the infiltration and differentiation of immune cells, manipulate the expression of immune checkpoints, and change the tumor immune microenvironment (TME). In this review, we briefly summarize several ways in which IR induces tumor cell death and discuss the interrelationship between RT-induced OS and antitumor immunity, with a focus on the interaction of ferroptosis with immunogenic death. We also summarize the potential mechanisms by which ROS regulates immune checkpoint expression, immune cells activity, and differentiation. In addition, we conclude the therapeutic opportunity improving radiotherapy in combination with immunotherapy by regulating OS, which may be beneficial for clinical treatment.